Excess cash holding, likuiditas, dan nilai perusahaan: Studi pada perusahaan non-finansial Indonesia - Felicia Santoso; Rita Juliana (Jurnal Manajemen Maranatha, 2021)
This study aims to investigate the effect of excess cash on liquidity and firm value. The sample that is used is 211 non-financial firms listed in Indonesia Stock Exchange (IDX) with period from 2007 to 2017, resulting a total of 2321 firm-year observations. The regression model used are fixed effect and random effect model. The results show that excess cash increase trading continuity and decrease liquidity risk. This result can be caused by uninformed trader trading participation. Additionally, excess cash has a positive effect on firm value directly because with excess cash firm can invest. The study also finds that the effect of excess cash on illiquid firm value is negative, this result happened because excess cash can increase firm’s information asymmetry problem. Finally, we also find that excess cash has higher effect on small size firms with financial constraint problems and higher growth opportunities.